Is the Restitution of Land Rights Amendment Bill aligned with the Constitution of South Africa? - Brand, Danie (Jacobus Frederick Daniel, 1968- ) (University of Pretoria, 2016)
Mini Dissertation (LLM)--University of Pretoria, 2015.